EFEKTIVITAS PELAKSANAAN MUTASI PNS DALAM PENYELENGGARAAN OTONOMI DAERAH (STUDI DI BADAN KEPEGAWAIAN, PENDIDIKAN DAN PELATIHAN DAERAH PROVINSI SULAWESI TENGAH) - Fitriyana, Fitriyana (Katalogis, 2013)
This study is aimed at recognizing efectivity of civil servant mutation at BKPPD Central of Celebes Province and in addition, to identify the dominan factors affecting the civil servant mutation. This research used deskriptive qualitatif method, which is expected to be able to present variables and the sign that was achieved for secondary data and primary data through in dept interview and observation in the research location (in BKPPD Centrall of Celebes Province). Variable chosen for explaning mutation are authority and procedural system. The informanÂ used in this study involves 7 people and Head of BKPPD as a Key Informan. The data analysis model is cualitative analysis to predict all datas, to reduction datas, to inspection the valid of datas, and the last is to explanation datas so that getted information needed. The independent variable or free variable is the mutation become the main indicator, first, legalicy is capable of someone or organization based on moral authorityÂ because profession formal, skilled, eithers norms or personal popularity to maked or do decition and to command obidient decition according to consecuent and second procedure system, to hokked with regulations client , to organize step or conduct a man out off organization whoâ€™s had interest towards organization activity. Based on the result research analysis, it can be said that the independency of intra-regional goverment mutationn in the autonomy era is fully continued ih the regions themselves, that seems as narrow regional cooptation related to other regions. This can be explained by the goverment official great authority of region.Mutation, Legalicy Capable, Procedure SystemMutation, Legalicy Capable, Procedure System